Intermediary Platforms – The Contractual Legal Framework - Marie Jull Sørensen (Nordic Journal of Commercial Law, 2018)
From a consumer protection perspective, this contribution analyses four contractual legal frames potentially applicable to the triangular contractual structure of online intermediary platforms. For each framework, criteria are derived, and it is discussed how and if these criteria are met in regards to intermediary platforms. The legal frameworks are 1. The Platform as employer; 2. The platform as the main contracting party; 3. The Platform as intermediary and 4. The platform as a secondary obligated party. It is discussed how the intermediary platforms challenge some of the basic considerations behind some of the legal frameworks. The contribution helps qualify the ongoing deliberations of legislators and academics on (re-)framing the legal frame(s) of intermediary platforms.